2014
DOI: 10.1080/15459624.2014.908260
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method for Designing and Fabricating Low-cost Facepiece Prototypes

Abstract: In 2010, the National Institute for Occupational Safety and Health (NIOSH) published new digital head form models based on their recently updated fit-test panel. The new panel, based on the 2000 census to better represent the modern work force, created two additional sizes: Short/Wide and Long/Narrow. While collecting the anthropometric data that comprised the panel, additional three-dimensional data were collected on a subset of the subjects. Within each sizing category, five individuals' three-dimensional da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…However, as previously published, hollow silicone models proved difficult to produce [14]. Studies have suggested a rotisserie method of manufacture in which the model is rotated while the silicone cures to ensure an even distribution of material [25, 26].…”
Section: Discussionmentioning
confidence: 99%
“…However, as previously published, hollow silicone models proved difficult to produce [14]. Studies have suggested a rotisserie method of manufacture in which the model is rotated while the silicone cures to ensure an even distribution of material [25, 26].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the use of cloth masks, researchers, and manufacturers have also paid attention to fabricating personal protective equipment (PPE), including masks and their components, by utilizing 3D printing (namely, Additive Manufacturing (AM)) to alleviate the shortage of surgical masks and respirators. [ 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 ] 3D printing is a novel and innovative rapid prototyping technology, and it can be used to fabricate complex geometric structures which connot be easily fabricated through traditional manufacturing process. [ 130 , 131 ] There are a host of various materials that can be used as the base material in 3D printing, such as polyamide (PA) composite, acrylonitrile butadiene styrene (ABS), nylon PA, polylactic acid (PLA), ULTEM (polyetherimide), and thermoplastic polyurethane (TPU).…”
Section: Choices Of Common Face Mask and Respiratormentioning
confidence: 99%
“…3D-printed polymer-based parts are increasingly used in various medical equipment and consumer products, where emissions from the printed part could present a health hazard or nuisance odors. Before the COVID-19 pandemic, researchers explored the use of 3D-printed respirators for applications such as better fitting face masks or medical implants, but this research rapidly accelerated from 2020 to 2021. ,, Additionally, 3D-printed parts are now frequently used in sensitive analytical instrumentation. , some of which are designed to measure pollutants that the parts themselves could emit . Uncharacterized emissions could potentially induce error, bias, or artifacts into measurements made with 3D-printed parts.…”
Section: Introductionmentioning
confidence: 99%